Case Report : CKD Stg V + Suspect Encapsulated Peritoneal Sclerosis - Risnandar Risnandar (Jurnal Ventilator, 2025)
This case report discusses a 54-year-old female patient diagnosed with Stage V Chronic Kidney Disease (CKD) undergoing Continuous Ambulatory Peritoneal Dialysis (CAPD). The patient presented with clinical symptoms such as nausea, vomiting, abdominal pain, and reduced ultrafiltration volume, raising suspicion of Encapsulated Peritoneal Sclerosis (EPS). EPS is a rare but serious complication in long-term CAPD patients. Management includes discontinuation of CAPD, adequate nutritional support, and symptomatic therapy. This report aims to enhance understanding of the diagnosis and management of EPS in Stage V CKD patients.